Cooling of male rat skeletal muscle during endurance‐like contraction attenuates contraction‐induced PGC‐1α mRNA expression - Daisuke Hoshino; Ryota Wada; Yutaro Mori; Reo Takeda; Yudai Nonaka; Ryotaro Kano; Ryo Takagi; Yutaka Kano (Physiological Reports, 2023)
Abstract This study aimed to determine effects of cooling on contraction‐induced peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α) and vascular endothelial growth factor (VEGF) gene expression, phosphorylations of its related protein kinases, and metabolic responses. Male rats were separated into two groups; room temperature (RT) or ice‐treated (COLD) on the right tibialis anterior (TA). The TA was contracted isometrically using nerve electrical stimulation (1‐s stimulation × 30 contractions, with 1‐s intervals, for 10 sets with 1‐min intervals). The TA was treated before the contraction and during 1‐min intervals with an ice pack for the COLD group and a water pack at RT for the RT group. The muscle temperature of the COLD group decreased to 19.42 ± 0.44°C (p < 0.0001, −36.4%) compared with the RT group after the experimental protocol. An increase in mRNA expression level of PGC‐1α, not VEGF, after muscle contractions was significantly lower in the COLD group than in the RT group (p < 0.0001, −63.0%). An increase in phosphorylated AMP‐activated kinase (AMPK) (p = 0.0037, −28.8%) and a decrease in glycogen concentration (p = 0.0231, +106.3%) after muscle contraction were also significantly inhibited by cooling. Collectively, muscle cooling attenuated the post‐contraction increases in PGC‐1α mRNA expression coinciding with decreases in AMPK phosphorylation and glycogen degradation.